(untitled) (International Journal of Physiotherapy, 2016)
Background: Non-invasive therapeutic approaches without negative side-effects are desirable in pain condition treatment where the mobility limiting factor is also there. Repetitive peripheral magnetic stimulation (rPMS) is considered a promising curative method from different perspectives. Because of wide range of therapeutic effects, therapy is mainly indicated in musculoskeletal and neurological disorders. Aim of this study was to investigate pain relief effect and improving of the difficulties in performing Activities of Daily Living (ADL) achived byrPMS among patients with acute and chronic conditions assosiated with musculoskeletal and neurological painful disorders. Methods: 40 patients (n=23 women, n=17 men) with acute and chronics painful condition and difficulty to perform ADL accompanying musculoskeletal or neurological disorders were comprised in the study. All patients were treated with rPMS. The therapy parameters were adjusted to patient´s condition. Patients with acute pain underwent daily treatments (n=5). Patients with chronic pain underwent treatments three times per week (n=10). The Pain presence was evaluated by a 10-point Visual Analog Scale (VAS) for Pain Presence (refer to Appendix 1). Difficulties to perform ADL were evaluated by Patient Functional Assessment Questionnaire (PFAQ) for ADL (refer to Appendix 2). A threemonth follow-up was completed. All collected data were further evaluated. Results: There was a statistically significant difference (p<0.05) in the before/after condition comparison. Majority of participants described pain decrease (87.33%) on VAS for Pain and improvement (41.33%) in ability to perform ADL after the course of treatment. A three-month follow up showed persisting improvement (to 42.04% (vs. before treatment condition)) in ADL performing abilities. Conclusion: Similar results proved that rPMS therapy can be used as an effective and non-invasive treatment of painful condition with ADL limiting factor accompanying musculoskeletal and neurological disorders. Persisting pain relief effect and ameliorating patient quality of life were observed.